Success factors for online food retail logistics - Anne Beckmann; Julia Kleineidam; Frank Straube (Data Science and Innovation in Supply Chain Management: How Data Transforms the Value Chain. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 29, 2020)
Purpose: While e-commerce in general has been growing rapidly for years, food e-commerce is lagging behind in Germany. The common approach of using traditional logistics systems and fulfilment concepts does not lead to long-term success. Con-sidering this problem, success factors are needed as a guideline for developing effec-tive fulfilment concepts for online food supply chains in the future. Methodology: Based on industry performance indexes as well as an extensive search via the google search engine about 20 case studies on online food fulfilment con-cepts are identified. The case studies are evaluated using a performance measure-ment concept. Information from the highest performing companies is used to deduct success factors for good practices in online food fulfilment. Findings: Three main groups of suppliers were identified: Full-range provider, niche suppliers (selective assortment with a specific focus) and supplier of cooking boxes. The fulfilment concept of online grocery retailers is described using thirteen catego-ries. Three success factors could be derived: Reduction of complexity, focus on online fulfilment, and offering a unique product-service mix. Originality: This paper contributes to the research areas of e-commerce and of lo-gistics and supply chain management, especially online food supply chains. In this area only little original scientific research exists. Also, the approach of using second-ary case studies is relatively new in this area of research and has yielded interesting results.
urn:nbn:de:gbv:830-882.0114835; hdl:10419/228914; https://econpapers.repec.org/RePEc:zbw:hiclpr:29
Keywords: 650; Logistics; Industry 4.0; Digitalization; Innovation; Supply Chain Management; Artificial Intelligence; Data Science